Update Breast Cancer 2022 Part 1 – Early Stage Breast Cancer - Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Fehm, Tanja N.; Belleville, Erik; Bader, Simon; Seitz, Katharina; Untch, Michael; Thill, Marc; Tesch, Hans; Ditsch, Nina; Lux, Michael P.; Aktas, Bahriye; Banys-Paluchowski, Maggie; Schneeweiss, Andreas; Harbeck, Nadia; Würstlein, Rachel; Hartkopf, Andreas D.; Wöckel, Achim; Seliger, Barbara; Massa, Chiara; Kolberg, Hans-Christian (Geburtshilfe und Frauenheilkunde, 2022)
Evidence relating to the treatment of breast cancer patients with early-stage disease has increased significantly in the past year. Abemaciclib, olaparib, and pembrolizumab are new drugs with good efficacy in the relevant patient groups. However, some questions remain unanswered. In particular, it remains unclear which premenopausal patients with hormone receptor-positive breast cancer should be spared unnecessary treatment. The question of the degree to which chemotherapy exerts a direct cytotoxic effect on the tumor or reduces ovarian function through chemotherapy could be of key importance. This group of patients could potentially be spared chemotherapy. New, previously experimental biomarker analysis methods, such as spatial analysis of gene expression (spatial transcriptomics) are gradually finding their way into large randomized phase III trials, such as the NeoTRIP trial. This in turn leads to a better understanding of the predictive factors of new therapies, for example immunotherapy. This review summarizes the scientific innovations from recent congresses such as the San Antonio Breast Cancer Symposium 2021 but also from recent publications.Die Erkenntnisse über die Behandlung von Mammakarzinompatientinnen mit frühen Krankheitsstadien haben im letzten Jahr deutlich zugenommen. Abemaciclib, Olaparib und Pembrolizumab sind neue Medikamente mit einer guten Wirksamkeit bei den entsprechenden Patientinnengruppen. Jedoch sind einige Fragestellungen nach wie vor unbeantwortet. Insbesondere welchen Patientinnen unnötige Therapien erspart werden können, ist bei prämenopausalen Patientinnen mit einem hormonrezeptorpositiven Mammakarzinom weiterhin unklar. Die Frage, inwieweit eine Chemotherapie einen direkten zytotoxischen Effekt auf den Tumor hat oder eher dadurch wirkt, dass die Ovarfunktion durch die Chemotherapie reduziert wird, könnte wegweisend sein. Dieser Patientinnengruppe kann möglicherweise eine Chemotherapie erspart bleiben. Neue, bislang experimentelle Biomarker-Analysemethoden, wie die räumliche Analyse der Genexpression (spatial transcriptomics), halten nach und nach Einzug in die großen randomisierten Phase-III-Studien, wie die NeoTRIP-Studie. Dies führt wiederum zum besseren Verständnis der prädiktiven Faktoren neuer Therapien, zum Beispiel der Immuntherapie. Diese Übersichtsarbeit fasst die wissenschaftlichen Neuerungen der aktuellen Kongresse wie dem San Antonio Breast Cancer Symposium 2021, aber auch von kürzlich veröffentlichten Publikationen zusammen.
Keywords: BRCA (breast cancer antigen); breast cancer; estrogen receptor; oral therapy